Costa Rica's Solidarity with Chilean Exiles: 1973-1988 - Rojas-Mejías, Diana (2021)
This article studies the solidarity groups that were formed in Costa Rica with the arrival of the Chilean exiles. During the period 1973-1988 three support networks were identified whose motives for struggle were different according to the time of their creation. Thus in early dates the support was concentrated in specific figures who sought the basic conditions for the exiles to settle in our country. Subsequently, a network was formed with political parties and social groups that denounced human rights violations through communiqués and acts of solidarity. Finally, another form of organization was found that focused on sending economic support to the Chilean resistance that was still fighting the dictatorship in the 1980's.